THE MEDIATING IMPACT OF SOCIAL MEDIA INTENSITY ON THE INFLUENCE OF ISLAMIC LEARNING AND SPIRITUAL INTELLIGENCE ON THE NEGATIVE INFLUENCE OF SOCIAL MEDIA - Mushthofa, Fathu Ni'am; Wathoni, Kharisul; Daryono, Rihab Wit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Apart from having a good impact on all aspects of life, social media also has a bad impact too. Starting from this anxiety, this research tries to map the factors that influence overcoming social media's negative impacts. This research aims to analyze and prove the importance of managing the intensity of social media use wisely to mediate Islamic learning and spiritual intelligence as an effective strategy to combat the negative influence of social media in the digital era on students. This research involved 66 class X students using a quantitative approach and survey methods. Data was collected through a Likert scale questionnaire, and data analysis was carried out using relevant statistical techniques. The research conclusion shows that the intensity of social media use mediates well the relationship between Islamic learning and spiritual intelligence on the negative influence of students' social media. The implications of this research highlight the importance of managing the intensity of social media use wisely and developing Islamic learning and spiritual intelligence to protect individuals from the negative influence of social media